KENDALA-KENDALA YANG DIALAMI MAHASISWA SELAMA DUDUK DI BANGKU KULIAH - Sudarto, Sudarto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The aim of this research is finding out the obstacles of that students encounter while attending the college. The respondents in this research were the PGSD FIP UNM Campus VI Bone students in the Even Semester 2023/2024, in totaling 57 people. The data collection instrument in this research was a questionnaire sheet. The data analysis techniques used are quantitative and narrative analysis techniques. Results and conclusions: the obstacles that many students encounter while attending college were: (1) the students cannot speak well in front of many people, (2) inability to divide or manage the time appropriately, (3) feeling lazy about reading books, (4) not understanding the material, and (5) not being able to make presentations well. Other obstacles, but only a few students experience them, were: (1) always relying on Google, (2) not being able to control themselves, (3) always relying on cellphones, (4) having difficulty in learning independently, (5) having difficulty in conveying ideas, (6) ) not being disciplined in doing the coursework, and (7) not being able to use formal language well.